Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

In showing that if $f,g\in L^p$, then $f+g\in L^p$, one can use the fact that $$|f+g|^p\leq 2^p\left(|f|^p + |g|^p\right).$$

The result I'd like help in proving is this:

Given that $1\lt p \lt \infty$, and $\forall ~s,t\in [0,\infty)$ $$\left(s+t\right)^p \leq 2^p\left(s^p+t^p\right).$$

Thank you.

share|improve this question
Do you mean $(s+t)^p\leq 2^p(s^p+t^p)$? –  Paul Nov 16 '11 at 8:29
Yes Paul. I'll edit to that effect. Thanks. –  Colin Nov 16 '11 at 8:35

3 Answers 3

up vote 7 down vote accepted

If I am not mistaken more is actually true. Since for $p>1$ the function $$f(x)=x^p$$ is convex, then by the midpoint inequality one has $$f\left(\frac{x+y}{2}\right)\leq \frac{f(x)+f(y)}{2}.$$ This translates immediately in $$(x+y)^p\leq 2^{p-1}(x^p+y^p),$$ which in turn imply your thesis. The case left is then $p=1$ but in this case the result is trivial.

Note that one can say more even in the case $0\leq p<1$. Indeed $\forall t\in [0,+\infty)$ one gets $$(1+t)^p\leq 1+t^p.$$ To prove the result define $$k(t)=(1+t)^p-t^p.$$ Then $\forall t\in (0,+\infty)$, we have $$k'(t)=p[(t+1)^{p-1}-t^{p-1}]<0,$$ and $$\lim_{t\to 0}\:k(t)=1,$$ therefore the claim follows. Now set $$t=\frac{x}{y}$$ to conclude $$(x+y)^p\leq x^p+y^p.$$

EDIT: According to Martin Sleziak's comment, this imply in turn that the function $$f(x)=x^p$$ is subadditive for $p<1$.

To collect all the informations all at once, one usually says that $\forall p\in [0,+\infty)$ it is true that $$(x+y)^p\leq \max(1,2^{p-1})(x^p+y^p).$$

share|improve this answer
Nice. Perhaps it's worth mentioning that what you proved in the second part is that the function $f(x)=x^p$ is subadditive for $p<1$. –  Martin Sleziak Nov 16 '11 at 12:06

So you want to prove: Given that $ 1 < p < \infty $ and $ \forall s,t \in [0,\infty) $

$(s+t)^p \le 2^p(s^p+t^p) $


$ (s+t)^p \le (2 \max(s,t))^p \le 2^p (s^p+t^p) $

and you're done.



share|improve this answer

The stronger (and optimal) result is that, for every $\color{red}{p\geqslant1}$ and nonnegative $s$ and $t$, $$ \color{red}{(s+t)^p\leqslant2^{p-1}(s^p+t^p)}. $$ A simple method of proof is to note that one wants to show that $c\left(\frac12(s+t)\right)\leqslant\frac12\left(c(s)+c(t)\right)$, where $c$ denotes the function defined on $x\geqslant0$ by $c(x)=x^p$, that this inequality is the midpoint property for a convex function, and that $c$ is indeed convex for every $p\geqslant1$.

share|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.